WhatsApp for English Language Learning of University Students - Maknunah , Salma Lu’lu’ah; Rizal, Daviq (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
Teachers must be conscious of adapting educational philosophies and practices to new generations of learners. One of the social media used is WhatsApp. WhatsApp is currently often used for English learning by students. This research aims to analyze the effectiveness of WhatsApp as an English learning medium for students. The data source for finding social problems in this research uses a qualitative approach using a descriptive design. The subjects of this research were 67 State Islamic University students from several faculties, with an age range of 18 to 25 years. Data collection in this research used questionnaires and interviews. The results of these two methods will be integrated holistically to present a comprehensive and in-depth picture of the phenomenon being studied. The results of this research were that 79.1% of 67 students concluded that it was effective and 20.1% considered it less effective than WhatsApp for learning. The use of WhatsApp is effective as an English learning medium for students because WhatsApp is an application that is often used so it is very easy to use as a learning medium.